Hickam's Dictum: Pseudoxanthoma elasticum and Usher syndrome in a single patient. (2nd September 2020) - Wang, Kevin; Statler, Brittney; Ramos, Michael; DeBenedictis, Meghan J; Babiuch, Amy; Yuan, Alex; Traboulsi, Elias I.
ABSTRACT: Background: To report the case of a patient with two distinct genetic systemic diseases – pseudoxanthoma elasticum (PXE) and Usher syndrome – confirmed by genetic testing. Materials and Methods: Single Retrospective Case Report Results: A 36-year-old woman presented with acute central vision loss of the left eye (OS). Fundus exam revealed choroidal neovascularization OS in the setting of angioid streaks secondary to an underlying diagnosis of PXE. Unexpectedly, she also exhibited peripheral bony spicules with significant visual field constriction. Physical exam revealed skin papules on her neck and hearing loss. The presence of angioid streaks and skin findings was compatible with PXE; the etiology of her pigmentary retinopathy and hearing loss was elucidated using genetic testing. The patient was found to be compound heterozygous for pathogenic variants in both the ABCC6 and USH2A genes, confirming the diagnosis of two rare disorders in a single patient. Conclusions: PXE and Usher syndrome are rare systemic disorders that cause distinctive retinal abnormalities. This report highlights the importance of genetic testing in diagnosing uncommon hereditary retinal disorders and outlines the progression of disease over 6 years.